1996
DOI: 10.1097/00004647-199611000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Transformation and Microvascular Integrity during Focal Cerebral Ischemia/Reperfusion

Abstract: Hemorrhagic transformation after cerebral ischemia is a well known clinical concern. The frequency of intact basal lamina (BL), identified by laminin antigen, in hemorrhagic and nonhemorrhagic zones after middle cerebral artery occlusion (MCA:O) and 3-h MCA:O with reperfusion in adolescent male baboons was assessed. Parenchymal hemoglobin was not detected prior to 24-h reperfusion. A significant decrease in the density of laminin (BL) in hemorrhagic zones (6.2 +/- 2.4) compared with nonhemorrhagic ischemic zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
178
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(188 citation statements)
references
References 25 publications
4
178
0
4
Order By: Relevance
“…This led the authors to postulate that later development of HT probably resulted from early ischemic damage to the endothelium. More recent studies by Hamann et al support this view, noting that reperfusion of ischemic tissue caused structural damage to the basal lamina (BL), an important part of the BBB complex (33,34). They concluded that this loss of BL structure in conjunction with breakdown of the extracellular matrix was probably necessary for the extravasation of plasma including proteins and, at later times, the formed elements of blood such as platelets and RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…This led the authors to postulate that later development of HT probably resulted from early ischemic damage to the endothelium. More recent studies by Hamann et al support this view, noting that reperfusion of ischemic tissue caused structural damage to the basal lamina (BL), an important part of the BBB complex (33,34). They concluded that this loss of BL structure in conjunction with breakdown of the extracellular matrix was probably necessary for the extravasation of plasma including proteins and, at later times, the formed elements of blood such as platelets and RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies and biomarker analyses have suggested that neuroinflammatory markers are linked to blood‐brain barrier (BBB) breakdown and HT risk 11, 31, 32, 33. Disruption of the BBB has been shown to be associated with neuroinflammation following ischemic injury,32 and hemorrhagic transformation has been reported as a maker of BBB breakdown 33. The ligand for ST2, IL‐33, is hypothesized to serve as an acute inflammatory signaling molecule that participates in maintaining barrier function and integrity 34.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the integrity of the cerebral microvasculature is provided mainly by 2 differing anatomical and functional barriers, ie, the blood-brain barrier (BBB) and basal lamina. 15 The BBB is represented by the interendothelial cell tight junctions. The basal lamina consists of a network of type IV collagen and laminin polymer connected by entactin and serves as a structural barrier to the extravasation of cellular blood elements.…”
Section: Discussionmentioning
confidence: 99%